DIAGNOSTIC IMAGING APPROACHES FOR SUBACROMIAL IMPINGEMENT SYNDROME - Akhundova, A.Y. (World of Medicine and Biology, 2025)
This study presents a structured diagnostic algorithm for subacromial impingement syndrome, incorporating radiography, MRI, and CT imaging, with a focus on diagnostic accuracy and treatment planning. MRI demonstrated high specificity (100 %) and moderate sensitivity (79 %) for subacromial impingement syndrome, with 76 % overall accuracy. Fracture evaluation showed 84 % accuracy, with CT and 3D reconstruction proving valuable in assessing fragment displacement. Imaging revealed tendon ruptures, joint space narrowing, fluid accumulation, and edema in key anatomical regions. The algorithm facilitated early diagnosis and guided appropriate intervention, leading to favorable clinical outcomes. Its application in post-traumatic cases enabled precise localization of pathology, supporting both surgical and conservative management strategies. These findings underscore the importance of multimodal imaging and structured diagnostic pathways in optimizing outcomes for patients with subacromial impingement syndrome, and related shoulder injuries.